On the repulsion effect of coupled Lamb waves modes - Nicolai, Marcel; Bulling, Jannis; Lugovtsova, Yevgeniya; Zeipert, Henning; Prager, Jens; Henning, Bernd

Diagnostics and Prognostics for Retrofitted Systems: A Comprehensive Approach for Enhanced System Health Assessment - Bender, Amelie; Aimiyekagbon, Osarenren Kennedy; Sextro, Walter (Proceedings of the 2024 Prognostics and System Health Management Conference (PHM))
Predicting the remaining useful life of technical systems has gained significant attention in recent years due to increasing demands for extending the lifespan of degrading system components. Therefore, already used systems are retrofitted by integrating sensors to monitor their performance and functionality, enabling accurate diagnosis of their condition and prediction of their remaining useful life. One of the main challenges in this field is identified in the missing data from the time where the retrofitted system has already run but without being monitored by sensors. In this paper, a novel approach for the combined diagnostics and prognostics of retrofitted systems is proposed. The methodology aims to provide an accurate diagnosis of the system’s health state and estimation of the remaining useful life by a combination of a machine learning and expert knowledge. To evaluate the effectiveness of the proposed methodology, a case study involving a retrofitted system in an industrial setting is selected and applied. It is demonstrated that the approach effectively diagnose the current system’s health state and accurately predict its remaining useful life, thereby enabling predictive maintenance and decision-making. Overall, our research contributes to advancing the field of condition monitoring for retrofitted systems by providing a comprehensive methodology that addresses the challenge of missing data.
Keywords: retrofit; diagnosis; prognostics; RUL prediction; missing data; ball bearings

Krieg aus Perspektive des Christentums. Dürfen Christ:innen Krieg rechtfertigen? - Leven, Eva-Maria; Grössl, Johannes (RELIGION 5-10)

𝜆Grapher: A Resource-Efficient Serverless System for GNN Serving through Graph Sharing - Hu, Haichuan; Liu, Fangming; Pei, Qiangyu; Yuan, Yongjie; Xu, Zichen; Wang, Lin (Proceedings of the ACM Web Conference (WWW))

Von der Entwicklung von Open Educational Resources zur Umsetzung von Open Educational Practices in der inklusiven Lehrkräftebildung: Anforderungen und Lösungswege am Beispiel der Projekte Inklud.nrw und InDigO - Büker, Petra; Kamin, Anna-Maria; Glawe, Katrin; Herding, Jana; Schaper, Franziska (MedienPädagogik)

IPA: Inference Pipeline Adaptation to Achieve High Accuracy and Cost-Efficiency - Ghafouri, Saeid; Razavi, Kamran; Salmani, Mehran; Sanaee, Alireza; Lorido Botran, Tania; Wang, Lin; Doyle, Joseph; Jamshidi, Pooyan (Journal of Systems Research (JSys))

Teaching and Learning of Microgrids for Secondary School Learners – a Renewable Energy Sustainability Strategy for East African Communities - Bogere, Paul; Belov, Alexander; Temmen, Katrin (Proceedings - First International Conference on Sustainable Energy Education (SEED 2024))

On restricted averages of Dedekind sums - Minelli, P.; Sourmelidis, A.; Technau, Marc (Int. Math. Res. Not. IMRN)

A Didactic Framework for Microgrids Knowledge Transfer – The Case of East Africa - Bogere, Paul; Temmen, Katrin (2024 IEEE Global Engineering Education Conference (EDUCON))

Brauchen wir ein ESE-Curriculum in der inklusiven Schule? – Ein Exkurs in die Konzeption eines Mehrebenenansatzes zur Prävention von Verhaltensproblemen in der Sekundarstufe I - Zdoupas, Philippos (ESE 6 (2024): In den Fokus ver-rückt – hidden topics im Förderschwerpunkt Emotionale und Soziale Entwicklung)
Die überdauernd hohen Prävalenzraten von Verhaltensstörungen und -problemen im Kindes- und Jugendalter verweisen auf einen verstärkten pädagogischen Handlungsbedarf und unterstreichen die Bedeutsamkeit präventiver Maßnahmen in der Schule. Wenngleich metaanalytische Befunde die grundsätzliche Wirksamkeit evidenzbasierter Präventionsprogramme bestätigen, so scheint der strukturelle Transfer in die pädagogische Praxis oftmals erschwert. Mit dem vorliegenden Beitrag werden die ersten konzeptionellen Ansätze eines schulweiten und curricular verankerten Präventionskonzepts zur Förderung emotionaler und sozialer Kompetenzen unter Berücksichtigung zweier methodischer Zugänge nachgezeichnet.

Social impacts of inclusive education: On the requirement for an emphasis on girls with emotional and behavioral disorders (EBD) in research on inclusion - Zdoupas, Philippos; Laubenstein, Désirée (Societal Impacts)

Remark on the Farey fraction spin chain - Technau, Marc (Proc. Amer. Math. Soc.)

The structural power of reconfigurable circuits in the amoebot model - Padalkin, Andreas; Scheideler, Christian; Warner, Daniel (Natural Computing)
Abstract The amoebot model (Derakhshandeh et al. in: SPAA ACM, pp 220–222. https://doi.org/10.1145/2612669.2612712 , 2014) has been proposed as a model for programmable matter consisting of tiny, robotic elements called amoebots . We consider the reconfigurable circuit extension (Feldmann et al. in J Comput Biol 29(4):317–343. https://doi.org/10.1089/cmb.2021.0363 , 2022) of the geometric amoebot model that allows the amoebot structure to interconnect amoebots by so-called circuits . A circuit permits the instantaneous transmission of signals between the connected amoebots. In this paper, we examine the structural power of the reconfigurable circuits. We start with fundamental problems like the stripe computation problem where, given any connected amoebot structure S , an amoebot u in S , and some axis X , all amoebots belonging to axis X through u have to be identified. Second, we consider the global maximum problem , which identifies an amoebot at the highest possible position with respect to some direction in some given amoebot (sub)structure. A solution to this problem can be used to solve the skeleton problem , where a cycle of amoebots has to be found in the given amoebot structure which contains all boundary amoebots. A canonical solution to that problem can be used to come up with a canonical path, which provides a unique characterization of the shape of the given amoebot structure. Constructing canonical paths for different directions allows the amoebots to set up a spanning tree and to check symmetry properties of the given amoebot structure. The problems are important for a number of applications like rapid shape transformation, energy dissemination, and structural monitoring. Interestingly, the reconfigurable circuit extension allows polylogarithmic-time solutions to all of these problems.

Carbon dioxide capture by aqueous glucosamine solutions: Pilot plant measurements and a theoretical study - Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny Y. (AIChE Journal)
Abstract A comprehensive investigation of the potential of aqueous glucosamine solutions as an eco‐friendly solvent for CO 2 capture was performed. It includes an experimental study in a pilot plant setup and a theoretical analysis with a rate‐based model. The model was validated against the measured column profiles of temperature and CO 2 concentration in both liquid and gas phases. Model‐based parameter sensitivity studies revealed inherent challenges for an effective absorption process. A slow reaction rate and suboptimal chemical equilibrium conditions were identified as key limitations, restricting the absorption efficiency and CO 2 loading capacity of the glucosamine solution. Furthermore, an analysis of the dissociation constant of this novel absorbent was performed and its significance with respect to the (limited) performance, capability, and efficiency evaluation was highlighted.

Tris(pentafluorophenyl)borane‐Catalyzed Functionalization of Benzylic C−F Bonds - Hoppe, Axel; Stepen, Arne J.; Köring, Laura; Paradies, Jan (Advanced Synthesis & Catalysis)
Abstract The activation of C( sp 3 )−F bonds by the commercially available catalyst B(C 6 F 5 ) 3 is reported and applied in reactions with arenes, allylic, vinylic and acetylenic silanes, and olefins to achieve a variety of C−C bond formations (45 examples).

Brief Announcement: Collision Detection for Modular Robots - It Is Easy to Cause Collisions and Hard to Avoid Them - Gupta, Siddharth; van Kreveld, Marc J.; Michail, Othon; Padalkin, Andreas (3rd Symposium on Algorithmic Foundations of Dynamic Networks, SAND 2024, June 5-7, 2024, Patras, Greece)

Reconfiguration and Locomotion with Joint Movements in the Amoebot Model - Padalkin, Andreas; Kumar, Manish; Scheideler, Christian (3rd Symposium on Algorithmic Foundations of Dynamic Networks, SAND 2024, June 5-7, 2024, Patras, Greece)

Polylogarithmic Time Algorithms for Shortest Path Forests in Programmable Matter - Padalkin, Andreas; Scheideler, Christian (Proceedings of the 43rd ACM Symposium on Principles of Distributed Computing)

Polylogarithmic Time Algorithms for Shortest Path Forests in Programmable Matter - Padalkin, Andreas; Scheideler, Christian (Proceedings of the 43rd ACM Symposium on Principles of Distributed Computing)

Technikbezogenen Sachunterricht inklusiv gestalten – eine empirische Untersuchung der Beschaffenheit und Berücksichtigung von Schülerbedürfnissen - Schröer, Franz; Schemel, Nele; Tenberge, Claudia (Teilhabe an gesellschaftlicher Transformation stärken: Der Beitrag der Arbeitsbezogenen und der Technischen Bildung)